Multiplicate compositions of the matrixes equivalent not to equal and opposite vectors - Кравец, Виктор Владимирович; Кравец, Тамила Викторовна; Харченко, Александр Валерьевич (Eastern-European Journal of Enterprise Technologies, 2010)
Multiplicative compositions of vectorial matrices are analyzed. Commutative, additively inverse and multiplicative inverse matrices are found. It is shown the procedure of matrix representation of multiplicative compositions of two and three vectors.